Professional Development of Teachers Which Work in Professional (Vocational) Education Institution: Andragogical Aspect - Sysko, Nataliia (Pedagogical Discourse, 2018)
The author states that in the process of professional development and improvement of teachers` professional skills which work in professional (vocational) education institutions it is necessary to take into account the specifics of adult education, which is based on the andragogical principles. Dependence of qualitative preparation of the student on the teacher’s professional and pedagogical competence is noted. It is noted that professional and pedagogical competence is achieved through continuous professional development during the entire career of a teacher. The approved normative legal documents regulating the education of adults are presented. The theoretical analysis of scientific works of foreign and native scientists is carried out. The characteristics of teachers` professional development are singled out. The focus is on the specifics of the adult learning process. The principles of adult education are highlighted. Attention is drawn to the need to take account of the specific training of adult personality in the process of professional development for teachers and professional (vocational) education. The necessity of formation of motivation for teachers to professional self-realization, increase of professional-pedagogical competence, development of professionally important qualities, professional reflection, career forecasting was noted. The necessity of introducing into the Classifier profession and providing of training in higher education institutions of teachers for the training of "adults" of students and androgens is emphasized. It was emphasized that the teaching of teachers will be successful provided that they acquire andragogical competence by those involved in the teachers` professional development of professional (vocational) education institutions.